(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The cause of high unemployment in India is a subject of intense debate among scholars. A group of scholars state that it is a consequence of "restrictive labor laws that create inflexibility in the labor market", while organized labor unions and another group of scholars contest this proposed rationale. India has about 250 labor regulations at central and state levels, and global manufacturing companies find the Indian labor laws to be excessively complex and restrictive compared to China and other economies that encourage manufacturing jobs. The Indian labor laws are "so numerous, complex and even ambiguous" that they prevent a pro-employment economic environment and smooth industrial relations. India needs "labor market reforms that address the needs of both employers and workers", and it should rewrite its labor laws that protects its workers, provides social security for workers between jobs, and makes compliance easier for the industry. This slow growth fails to provide enough unemployment opportunities to the increasing population. Constant increase in population has been a big problem in India. It is one of the main causes of unemployment.Agriculture is underdeveloped in India. It provides seasonal employment. Large part of population is dependent on agriculture. But agriculture being seasonal provides work for a few months. So this gives rise to unemployment. In big families having big business, many such persons will be available who do not do any work and depend on the joint income of the family.Unemployment is a curse to the society. It does not only impact the individuals but also the society as a whole. There are a number of factors that lead to unemployment. Here is a look at these factors in detail and also the possible solutions to control this problem.